Global Climate Change and Public Health 2013
DOI: 10.1007/978-1-4614-8417-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Vector-Borne Disease in the Amazon

Abstract: Impending changes in climate regimes coupled with anthropogenic changes in land use and land cover change pose the most pressing challenges to human societies and natural ecosystems. Global climate change is predicted to disrupt seasonal periodicities and long-term trends in rainfall and temperature, altering natural climate cycles and variation. The impact of environmental change on disease transmission will determine who, when, and where human livelihoods fl ourish and fail. Vulnerable populations will be pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Studies using TRMM have shown that areas of wetter conditions in the higher elevations of Uganda are often associated with increased incidence of Black Plague (MacMillan et al, 2012; Monaghan et al, 2012). TRMM and GPM estimates are also being used to characterize mosquito-breeding habitats in an effort to identify areas with higher disease risk (Valle et al, 2013;Pan et al, 2014;Zaitchik et al, 2014). Research applications will improve with GPM's increased spatio-temporal resolution and accuracy, helping to improve the environmental and climatic conditions for increased disease outbreaks.…”
Section: Disaster Response Extremes and Diseasementioning
confidence: 99%
“…Studies using TRMM have shown that areas of wetter conditions in the higher elevations of Uganda are often associated with increased incidence of Black Plague (MacMillan et al, 2012; Monaghan et al, 2012). TRMM and GPM estimates are also being used to characterize mosquito-breeding habitats in an effort to identify areas with higher disease risk (Valle et al, 2013;Pan et al, 2014;Zaitchik et al, 2014). Research applications will improve with GPM's increased spatio-temporal resolution and accuracy, helping to improve the environmental and climatic conditions for increased disease outbreaks.…”
Section: Disaster Response Extremes and Diseasementioning
confidence: 99%
“… Include Palmeiro-Silva, Y. 60 2020 Non-systematic review Chile There is limited evidence in Chile regarding the impact of climate change on health. High temperatures were associated with higher mortality risk in the elderly and there is greater exposure to heatwaves.…”
Section: Resultsmentioning
confidence: 99%
“… Include Palmeiro-Silva, Y. 60 2020 Non-systematic review Chile The number of heatwave exposures for the elderly has increased over time. Wildfire exposure has almost tripled when comparing the periods 2011–2004 and 2015–2018.…”
Section: Resultsmentioning
confidence: 99%
“…d The IMERG NRT data have also been used to track environmental conditions on the ground in order to predict and validate the risk of cholera infection (Khan et al 2017) and to characterize mosquitobreeding habitats in an effort to identify areas with higher disease risk (Pan et al 2014).…”
Section: Societal Benefitsmentioning
confidence: 99%